2020
DOI: 10.2478/exell-2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

English goes digital: Framing pre-service teachers’ perceptions of a learning management system in their EFL studies

Abstract: This article introduces and discusses an empirical investigation that aimed to establish how pre-service teachers of English (hereinafter “participants”) framed their perceptions of Canvas, a learning management system (LMS), in their studies of English as a Foreign Language (EFL). In the present study, the participants and their respective controls (i.e., non-teacher EFL students) were requested to write a short reflective essay associated with the use of the LMS in their EFL course. All participants and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
2
6
0
Order By: Relevance
“…Taken together, the findings of this mixed-methods research revealed that the overwhelming majority of the instructors held positive perceptions towards the use of lms in English classes. This finding can be taken as evidence for some studies which have shown the same results (Basal, 2015b;Kapranov, 2020;Toland et al, 2014). Nevertheless, some efl teachers do not favor using lms due to some obstacles such as the inappropriacy for productive skills, complexity of functions, students' unfamiliarity as well a lack of interest, and more importantly, inadequacy of teacher training programs.…”
Section: íKalasupporting
confidence: 55%
See 1 more Smart Citation
“…Taken together, the findings of this mixed-methods research revealed that the overwhelming majority of the instructors held positive perceptions towards the use of lms in English classes. This finding can be taken as evidence for some studies which have shown the same results (Basal, 2015b;Kapranov, 2020;Toland et al, 2014). Nevertheless, some efl teachers do not favor using lms due to some obstacles such as the inappropriacy for productive skills, complexity of functions, students' unfamiliarity as well a lack of interest, and more importantly, inadequacy of teacher training programs.…”
Section: íKalasupporting
confidence: 55%
“…Findings indicated that pre-service English teachers had positive perceptions about integrating lms into their on-site instruction by using various web 2.0 tools. The results of this study were ratified by Kapranov's (2020) study in which pre-service…”
Section: íKalamentioning
confidence: 58%
“…These two groups are gender-matched and similar in the age demographics (the participants' mean age = 24.0 y.o., standard deviation = 9.2; the controls' mean age = 26.1 y.o., standard deviation = 6.7). The similarity between them in terms of the demographics could be taken to assume that they belong to the so-called generation of the digital natives (From, 2017;Kapranov, 2020), who have grown up with digital technology. Consequently, it could be assumed that the participants' and controls' argumentative essays would be reflective of their knowledge and awareness of digital competence and, in particular, digital artifacts.…”
Section: Conclusion and Linguo-didactic Implicationsmentioning
confidence: 99%
“…Inspired by the omnipresence of digital artifacts in Norwegian primary school settings (Kapranov 2020;Krulatz, Steen-Olsen and Torgersen 2018;Krumsvik 2020;Tømte and Gjerustad 2020), this article presents and discusses a study that seeks to identify, analyse and classify discursive constructions of digital artifacts in the corpus of academic essays written on a range of topics in EFL didactics by a group of primary school EFL teachers (henceforth -participants). In concord with Lee, Thomas and Baskerville (2015), digital artifacts are broadly conceptualised in the study as a digital entity that is comprised of such components, as i) information (a message), ii) technology (hardware and software), and iii) a social act of communication (a contextually bound communicative act that takes place in a socio-cultural space).…”
Section: Introductionmentioning
confidence: 99%
“…Informed by Vygotsky's ( , 1981Vygotsky's ( , 1978 ideas associated with mediation and Wodak's (2012Wodak's ( , 2009 approach to discursive constructions, the study that is further described in the article explores how digital artifacts are constructed discursively by the participants, who are primary school EFL teachers. It should be noted that whereas the current literature (Bader, Iversen and Burner 2021;Kapranov 2022;Krulatz, Steen-Olsen and Torgersen 2018) addresses the use of digital artifacts by pre-service EFL teachers in Norway, analogous studies including in-service primary school EFL teachers remain unexplored (Kapranov 2020;Tømte and Gjerustad 2020: 260). Moreover, there seems to be no published research that specifically pays attention to discursive constructions of digital artifacts in academic essays written by in-service primary school EFL teachers.…”
Section: Introductionmentioning
confidence: 99%